Solve the system by substitution method

X=-4y+4

3x-7y=-7

X=-4y+4

3x-7y=-7

X=-4y+4

Therefore:

3(-4y+4)-7y=-7

-12y+12-7y=-7

12+7=7y+12y

19=19y

Therefore y=1.

When y=1,

x=-4(1)+4=-4+4=0.

You have the (X) in a single substitute the equation of the second equation. Then, in an expression have the same (Y). Is a linear equation that that is easily solved. After finding the back of the basis of the expression at the beginning.

\( \begin{cases}x=-4y+4\\3x-7y=-7\end{cases} \)

\( \begin{cases}x=-4y+4\\3(-4y+4)-7y=-7\end{cases} \)

\( \begin{cases}x=-4y+4\\-12y+12-7y=-7\end{cases} \)

\( \begin{cases}x=-4y+4\\-19y=-19|:(-19)\end{cases} \)

\( \begin{cases}x=-4*1+4\\y=1\end{cases} \)

\( \begin{cases}x=0\\y=1\end{cases} \)

RELATED: